Irresistibility : Secrets of Selling Yourself - Davies, Philippa (London Hodder & Stoughton, 2000)
In a world of change and instability, selling ourselves has never been more important. In this book, psychologist Philippa Davies' takes a look at aspects of irresistibility, offering practical advice on the psychology of influencing others, packaging yourself, and seeing off the competition.
Secrets of Selling Yourself.
Keywords: Self-actualization (Psychology) -- Success in business -- Career development